2018
DOI: 10.1016/j.jaip.2017.06.041
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal Dominant Hyper-IgE Syndrome in the USIDNET Registry

Abstract: BACKGROUND Autosomal dominant hyper-IgE syndrome (AD-HIES) is a rare condition. OBJECTIVE Data from the USIDNET Registry provide a resource to examine the characteristics of patients with rare immune deficiency diseases. METHODS A query was submitted to the USIDNET requesting deidentified data for patients with physician-diagnosed AD-HIES through July 2016. RESULTS Data on 85 patients diagnosed with AD-HIES (50 males; 35 females) born between 1950 and 2013, collected by 14 physicians from 25 states and Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
50
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 40 publications
10
50
1
Order By: Relevance
“…Cohen et al found no atopy in patients with AT. In HIES unspecified, AD‐HIES and AR‐HIES, all of the atopic symptoms, if reported, were present in about half of the patients . Renner et al described the presence of atopy in most Comèl‐Netherton patients.…”
Section: Resultsmentioning
confidence: 99%
“…Cohen et al found no atopy in patients with AT. In HIES unspecified, AD‐HIES and AR‐HIES, all of the atopic symptoms, if reported, were present in about half of the patients . Renner et al described the presence of atopy in most Comèl‐Netherton patients.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, STAT3 deficiency explains the delayed shedding of primary teeth, susceptibility to bone fractures, development of aneurysms and the coarse facial features which are hallmarks of Job syndrome. It is therefore not surprising that patients with AD‐HIES because of STAT3 mutations present with broad immunological and non‐immunological manifestations …”
Section: Stat3 Loss‐of‐function Mutations With Dominant Negative Effectmentioning
confidence: 99%
“…Neonatal onset eczema (present in 57% of patients), recurrent cutaneous staphylococcal infections with abscess formation (74%), recurrent pneumonias caused by Staphylococcus aureus (72%) and Aspergillus fumigatus (27%) often resulting in pneumatoceles, deep organ abscesses, mucocutaneous candidiasis (MCC), along with skeletal, dental and connective tissue abnormalities sum up the clinical features of AD‐HIES . While thought to be uncommon, a recent report listed food (37%) and environmental (18%) allergies as being present in a cohort of 58 patients with AD‐HIES collected in the USIDnet registry; nonetheless this is less frequent than reported by patients with DOCK8 deficiency, possibly related to impaired mast cell degranulation .…”
Section: Stat3 Loss‐of‐function Mutations With Dominant Negative Effectmentioning
confidence: 99%
See 2 more Smart Citations